1985
DOI: 10.1093/carcin/6.6.929
|View full text |Cite
|
Sign up to set email alerts
|

The radioprotector WR1065 reduces radiation-induced mutations at the hypoxanthine-guanine phosphoribosyl transferase locus in V79 cells

Abstract: N-(2-mercaptoethyl)-1,3-diaminopropane (WR1065) protects against radiation-induced cell killing and mutagenesis at the hypoxanthine-guanine phosphoribosyl transferase (HGPRT) locus in V79 Chinese hamster lung fibroblast cells. At a concentration of 4 mM, WR1065 was found to be effective in protecting against radiation-induced cell lethality only if present during irradiation, e.g., a dose modification factor (DMF) of 1.9. No protective effect was observed if the protector was added within 5 min after irradiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
65
0
2

Year Published

1987
1987
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(71 citation statements)
references
References 0 publications
4
65
0
2
Order By: Relevance
“…Two concentrations of WR1065 were chosen for investigation. WR1065 when present during irradiation at a concentration of 4 mM can significantly protect cells from radiation toxicity [12,13,27]. This effect is best described as immediate radioprotection and is routinely demonstrated by administering WR1065 30 min prior to irradiation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two concentrations of WR1065 were chosen for investigation. WR1065 when present during irradiation at a concentration of 4 mM can significantly protect cells from radiation toxicity [12,13,27]. This effect is best described as immediate radioprotection and is routinely demonstrated by administering WR1065 30 min prior to irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…This effect is best described as immediate radioprotection and is routinely demonstrated by administering WR1065 30 min prior to irradiation. The radioprotective effect, however, diminishes rapidly as the concentration of WR1065 is reduced [12,13,27]. At a concentration of 40 μM, WR1065 is ineffective for protection against cell killing but is sufficient for preventing radiation-induced mutagenesis through a distinctly separate mechanism of action [13].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggestion was confirmed by Milas et al (1984), who reported the anticarcinogenic effect of WR-2721 in irradiated mice. In addition, protectors have been shown to be antimutagenic (Grdina et al, 1985a; and antineoplastic (Hill et al, 1986) and to reduce the formation of radiation-induced preneoplastic foci in rats (Grdina et al, 1985b).…”
mentioning
confidence: 99%
“…Because some workers have suggested (Tilby et al, 1984;Evans et al, 1986) that DNA elution at pH9.6 modifies the quality of breaks, we assayed DSB formation both at pH 9.6 and pH7.2. (Grdina et al, 1985a;Nagy et al, 1986a (Meyn & Jenkins, 1983). In the DNA repair studies, a single cell suspension was irradiated, on ice, with a dose of 25krad (250Gy).…”
mentioning
confidence: 99%